Chapter «И скрипка, и контрабас»: фигура парадокса и поэтика недоумения в художественном мышлении Пиранделло и Достоевского - CHICHKINE, Andrei (Biblioteca di Studi Slavistici, 2023)
"Both violin and contrabass": The Figure of Paradox and the Poetics of Bewilderment in the Artistic Thinking of Pirandello and Dostoevsky. Pirandello and Dostoevsky are deeply linked at thematic, ideological and textual levels. In 1908, Pirandello published the treatise Humorism, in which he elaborated an original theory of humor and substantiated a worldview that is quite close to the type of artistic consciousness inherent in Dostoevsky's work, and is genetically related to it. The poetics of paradox, in which every mental and sensual experience is tested by its "opposite", encourages the reader to "hang" between two seemingly mutually exclusive principles while opening up the possibility of a new, more complex understanding of reality and of the Other. This article presents aspects of Pirandello's theory of humor in a new light, revealing their potential for application to the analysis of Dostoevsky's work.